PREVENTIVE EFFORTS FOR CORRUPTION CRIMINAL MEASURES THROUGH THE ROLE OF HIGH EDUCATION - Ismaya Hera Wardanie (Surakarta Law and Society Journal, 2020)
The purpose this study is to identify preventive measures for corruption through the role of higher education. This legal research used non-doctrinal. This type of study is a scientific study with the intention of only wanting to learn not to teach a doctrine, so the method is referred to as a nondoctrinal method. The result indicated that the problem of limiting corruption can not only be done by law enforcement officials, it is expected that the world of education can play a role in preventing corruption early on. Education as a forum to form the next generation of the nation becomes an effective forum for preventing corruption. Eradicating corruption is not enough to punish and give lectures or anti-corruption seminars. In order to avoid growing corruption in Indonesia, it is necessary to look for it from the root of the problem. Providing adequate anti-corruption education will provide protection to prospective future generations of the nation from the rampant acts of corruption. The subject of this study is to identify preventive measures for corruption through the role of higher education. To against the corruption is the responsibility of all components of the state and if only one of the parts is weak, it could be an obstacle to the effort to fight corruption. One of the preventive efforts of corruption starts from the important role in higher education as the land of integrity that will create individual characters. Evaluation Results from the policy of against corruption in higher education is effective because all indicators of effectiveness are in the policy. Keywords: corruption, high education, preventive effort.